"Internet and Queer Identity" seminar syllabus. - Hotaling, Katrina. (Tufts University. Tisch Library., 2021)
Syllabus for a 4-class seminar "Internet and Queer Identity". The goal for this class will be to use the online MOGAI and asexual communities to show how an online space and the discourse that came along with it allowed young queer people on the internet to shape their identities and grow into the young adult queer people of today.; Keywords: Internet, LGBTQ, Queer, Identity.; This microseminar was created for Tufts University course WGSS072 Intro to Women's, Gender, and Sexuality Studies: Queering Feminisms (Spring 2021, Professor Anna Christine)